Type-specific incidence, clearance and predictors of cervical human papillomavirus infections (HPV) among young women: a prospective study in Uganda - Banura, Cecily (BioMed Central, 2010)
BACKGROUND: While infections with human papillomavirus (HPV) are highly prevalent among sexually active young women in Uganda, information on incidence, clearance and their associated risk factors is sparse. To estimate the incidence, prevalence and determinants of HPV infections, we conducted a prospective follow-up study among 1,275 women aged 12-24 years at the time of recruitment. Women answered a questionnaire and underwent a pelvic examination at each visit to collect exfoliated cervical cells. The presence of 42 HPV types was evaluated in exfoliated cervical cells by a polymerase chain based (PCR) assay (SPF10-DEIA LiPA). RESULTS: Three hundred and eighty (380) of 1,275 (29.8%) women were followed up for a median time of 18.5 months (inter-quartile range 9.7-26.6). Sixty-nine (69) women had incident HPV infections during 226 person-years of follow-up reflecting an incidence rate of 30.5 per 100 person-years. Incident HPV infections were marginally associated with HIV positivity (RR = 2.8, 95% CI: 0.9 - 8.3). Clearance for HPV type-specific infections was frequent ranging between 42.3% and 100.0% for high- and 50% and 100% for low-risk types. Only 31.2% of women cleared all their infections. Clearance was associated with HIV negativity (Adjusted clearance = 0.2, 95% CI: 0.1 - 0.7) but not with age at study entry, lifetime number of sexual partners and multiplicity of infections. The prevalence of low-grade squamous intraepithelial lesions (LSILs) was 53/365 (14.5%). None of the women had a high-grade cervical lesion (HSIL) or cancer. Twenty-two (22) of 150 (14.7%) HPV negative women at baseline developed incident LSIL during follow-up. The risk for LSIL appeared to be elevated among women with HPV 18-related types compared to women not infected with those types (RR = 3.5, 95% CI: 1.0 - 11.8). CONCLUSIONS: Incident HPV infections and type-specific HPV clearance were frequent among our study population of young women. These results underscore the need to vaccinate pre-adolescent girls before initiation of sexual activity.